1980-2015. Una separazione radicale dal passato - Anzilotti, Carlo (Il sogno della farfalla, 2026)
The aim of this article is to retrace a pivotal moment in the history of the Collective Analysis, during October 1980, when sessions took place at the University of Rome. That year marked the emergence of a psychological crisis within this large group, which manifested in distinctive and often dramatic forms within the psychotherapeutic relationships established with Fagioli. To elucidate the dynamics that unfolded during these seminars, the author integrates Fagioli’s theoretical elaborations, up to his most recent writings, with personal memories of crucial moments of the crisis and experiences from the therapy sessions.